Tobacco use in India: prevalence and predictors of smoking and chewing in a national cross sectional household survey - Rani, M (BMJ Group, 2003)
Objective: To estimate the prevalence and the socioeconomic and demographic correlates of tobacco consumption in India. Design: Cross sectional, nationally representative population based household survey. Subjects: 315 598 individuals 15 years or older from 91 196 households were sampled in National Family Health Survey-2 (1998–99). Data on tobacco consumption were elicited from household informants. Measures and methods: Prevalence of current smoking and current chewing of tobacco were used as outcome measures. Simple and two way cross tabulations and multivariate logistic regression analysis were the main analytical methods. Results: Thirty per cent of the population 15 years or older—47% men and 14% of women—either smoked or chewed tobacco, which translates to almost 195 million people—154 million men and 41million women in India. However, the prevalence may be underestimated by almost 11% and 1.5% for chewing tobacco among men and women, respectively, and by 5% and 0.5% for smoking among men and women, respectively, because of use of household informants. Tobacco consumption was significantly higher in poor, less educated, scheduled castes and scheduled tribe populations. The prevalence of tobacco consumption increased up to the age of 50 years and then levelled or declined. The prevalence of smoking and chewing also varied widely between different states and had a strong association with individual's sociocultural characteristics. Conclusion: The findings of the study highlight that an agenda to improve health outcomes among the poor in India must include effective interventions to control tobacco use. Failure to do so would most likely result in doubling the burden of diseases—both communicable and non-communicable—among India's teeming poor. There is a need for periodical surveys using more consistent definitions of tobacco use and eliciting information on different types of tobacco consumed. The study also suggests a need to adjust the prevalence estimates based on household informants